2021
DOI: 10.3390/nano11020507
|View full text |Cite
|
Sign up to set email alerts
|

Germanium Nanowires as Sensing Devices: Modelization of Electrical Properties

Abstract: In this paper, we model the electrical properties of germanium nanowires with a particular focus on physical mechanisms of electrical molecular sensing. We use the Tibercad software to solve the drift-diffusion equations in 3D and we validate the model against experimental data, considering a p-doped nanowire with surface traps. We simulate three different types of interactions: (1) Passivation of surface traps; (2) Additional surface charges; (3) Charge transfer from molecules to nanowires. By analyzing simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…To ensure the changes in the IV response are due to the protein binding and are repeatable, two reference devices were made and tested (see Supporting Information). Previous simulations on Ge NWs have shown that, if molecular charge transfer of holes with a density of 10 18 cm −3 occurs from the surface of the NW, this could result in a theoretical enhancement of up to 400% in the current under a bias of 0.1 V. 31 The results we observe here suggest that a similar transfer of charge may occur from the protein to the NWs. To quantify the changes in current with the concentration of the spike protein, the relative change in current at a fixed bias point (±2 V) is plotted as a function of the concentration, as shown in Figure 7b.…”
Section: ■ Results and Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…To ensure the changes in the IV response are due to the protein binding and are repeatable, two reference devices were made and tested (see Supporting Information). Previous simulations on Ge NWs have shown that, if molecular charge transfer of holes with a density of 10 18 cm −3 occurs from the surface of the NW, this could result in a theoretical enhancement of up to 400% in the current under a bias of 0.1 V. 31 The results we observe here suggest that a similar transfer of charge may occur from the protein to the NWs. To quantify the changes in current with the concentration of the spike protein, the relative change in current at a fixed bias point (±2 V) is plotted as a function of the concentration, as shown in Figure 7b.…”
Section: ■ Results and Discussionsupporting
confidence: 71%
“…The presence of the bound aptamers on the NWs has introduced a charge distribution across the NW surface, which in turn results in an induced charge depletion within the NWs and the observed current reduction. This behavior has previously been modeled by adding p-type charges to the surface of NWs and as such suggests that the overall net charge from the aptamers used here is p-type.…”
Section: Resultsmentioning
confidence: 99%
“…2 In the field of energy conversion and storage, nanowire structures can incomparably increase energy density, power density, and cycling performance because of their larger surface-to-volume ratio, extra active sites, and better permeability. 3 Among the candidate materials for semiconductor nanowires, germanium (Ge) has its own advantages, 4,5 as it has a similar diamond structure to silicon, 6 higher electron and hole mobilities as well as a larger Bohr exciton radius. 7 Many nanowire synthesis methods have been proposed and intensively studied, 8−11 to obtain desired nanowire structures at high precision and efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 ] It has been demonstrated that Ge NW may be used in Li‐ and Na‐ion batteries, [ 2,3 ] thermoelectricity, [ 4 ] photodetectors, [ 5,6 ] and sensors. [ 7,8 ] The most commonly used technique for the fabrication of semiconducting Ge NW is vapor deposition. [ 9 ] However, vapor–liquid–solid methods require high‐energy density and rather toxic reagents and complex equipment.…”
Section: Introductionmentioning
confidence: 99%